Microbend in an SMS Fiber Structure - Fitri Rahmah; Sekartedjo Sekartedjo; Agus Muhamad Hatta (Institut Teknologi Sepuluh Nopember, 2015)
We present a numerical and experimental model of microbend in an SMS fiber structure. We obtain the numerical model by using several boundary conditions in SMS fiber structure. These conditions divided into transmission of light in a straight multimode fiber and in a bend multimode fiber. The microbend in multimode fiber affects the radius of curvature of the fiber. Thus, causes radiation several modes and then re-distribution of guided modes. The guided modes itself will vary in MMI and bring out different output power. The numerical result compare well with the experimental result from variation of the radius of curvature of the fiber (R) and the arc length.